Reliability analysis of the cast-in-place bored pile with different defects - Yao, Hua; Ma, Lemin; Duan, Zhiqiang; Guo, Wei (Frontiers in Built Environment, 2024)
The defects of the cast-in-place bored piles heavily influence their integrities and bearing capacities. The bearing capacity and reliability index of the cast-in-place bored piles with different defects was studied using finite element method. The accuracy of the numerical model is verified by the field tests results of an in-situ cast-in-place bored piles. Parametric studies are conducted to investigate the toe debris, mud cake, necking and bulging defects on the ultimate bearing capacities of the cast-in-place bored piles.The results indicate that maximum reductions of the ultimate bearing capacities of the cast-in-place bored pile with toe debris defect decrease by 17%, with mud cake defect decrease by 19%, with necking defect by 6.1%, while that with pile bulging defect increase by 40.9%. The minimum reliability index can be 0.81 when the diameter of pile necking defect is 0.2 m. The maximum reliability index can be 3.63 when the diameter of pile necking defect is 2.0 m.